Stress-inducible IL-6 is regulated by KLF7 in brown adipocytes. Issue 4 (April 2023) - Tang, Yihan; Ma, Dingling; Liang, Maodi; Hou, Yanting; Zhang, Meixiu; Wang, Jingzhou; Yuan, Chenggang; Li, Menghuan; Sun, Chaoyue; Xie, Jianxin; Wang, Cuizhe; Zhang, Jun
Abstract: Stress-inducible interleukin 6 (IL-6) is generated in brown adipocytes via beta-3 adrenergic receptor (ADRB3) signaling, which is necessary in stress hyperglycemia, the kind of metabolic adaptation enabling "fight or flight" response by means of liver gluconeogenesis. Nevertheless, the mechanism of ADRB3 signaling mediates IL-6 in brown adipocytes remains unclear. As a result, it is critical to understand how brown adipocytes produce IL-6 via ADRB3 signaling. We found that the ADRB3 agonist and cold stimulation promoted the expression of KLF7 and IL-6 in brown adipocytes of mice. In parallel to these results in vivo, treatment with ADRB3 agonist promoted the expression of KLF7 and the release of IL-6 in primary brown adipocytes of mice. Notably, we discovered that KLF7 positively controls the expression of IL-6 and downregulated KLF7 largely blunted ADRB3 agonist induced IL-6 expressions in brown adipocytes. Our findings suggest that KLF7 is required for the generation of IL-6 when ADRB3 signaling is activated in brown adipocytes.